2021
DOI: 10.1155/2021/6670219
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of Toxoplasma gondii Infection among Pregnant Women in Kumasi: A Cross-Sectional Study at a District-Level Hospital, Ghana

Abstract: Background. This study investigated the prevalence and risk factors of Toxoplasma gondii infection among pregnant women in a district-level hospital in Ghana and compared the diagnostic performance of the rapid diagnostic test (RDT) and enzyme-linked immunosorbent assay (ELISA) for T. gondii diagnosis. Method. This cross-sectional study included 400 consecutive consenting women in their first-trimester stage of pregnancy. A validated well-structured closed-ended questionnaire was used to collect sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…This finding is consistent with reports from various parts of the world, suggesting that the source of drinking water can impact the transmission of Toxoplasma 52 . Recently, Okojokwu et al 2023 43 discovered a greater frequency among those who use pipe-borne water as their source of drinking water, and the same was reported by Singh et al 2021 39 .…”
Section: Risk Factors Associated With Toxoplasmosis Among the Samples...mentioning
confidence: 69%
See 1 more Smart Citation
“…This finding is consistent with reports from various parts of the world, suggesting that the source of drinking water can impact the transmission of Toxoplasma 52 . Recently, Okojokwu et al 2023 43 discovered a greater frequency among those who use pipe-borne water as their source of drinking water, and the same was reported by Singh et al 2021 39 .…”
Section: Risk Factors Associated With Toxoplasmosis Among the Samples...mentioning
confidence: 69%
“…Robert-Gangneux et al 38 revealed that toxoplasmosis seroprevalence among patients with cerebral, pulmonary, and post-transplant toxoplasmosis were (100%, 90%, and 89%, respectively). In contrast, lower rates were observed in the levels of IgG and IgM in serum samples among pregnant women (57.3%, and 3.5%, respectively) 39 .…”
Section: Serological Analysismentioning
confidence: 79%
“…During pregnancy, early infection with T. gondii increases the risk of foetal transmission, with an increase between 60% and 81% in the third trimester [42,43]. Infections in the first trimester can be severe, resulting in abnormalities in foetal development or abortion [25]. When infection occurs in the third trimester, 80% of new-borns are asymptomatic [44].…”
Section: Discussionmentioning
confidence: 99%
“…A polymerase chain reaction confirms current infections [29]. Early detection of the infection is crucial in preventing negative consequences on the pregnancy and her unborn child [25]. We describe the seropositivity of T. gondii among pregnant women attending antenatal care at a general hospital in Atwima‐Nwabiagya District, Ghana.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation